Assessment of Alternative Personal Protective Equipment by Emergency Department Personnel During the SARS-CoV-2 Pandemic: A Simulation-Based Pilot Study. Issue 6 (December 2020) - Shavit, Danielle; Feldman, Oren; Hussein, Khetam; Meir, Michal; Miller, Asaf; Gutgold, Amichai; Idelman, Ravit; Kvatinsky, Noa; Cohen, Daniel M.; Shavit, Itai
Abstract : Summary Statement: Shortage of personal protective equipment (PPE) for frontline healthcare workers managing the current severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic is a major, global challenge. In this pilot study, we describe a simulation-based method for evaluating the suitability and acceptability of an alternative biological isolation garment (BIG, a gown or a suit) for clinical use by emergency department (ED) personnel. Using a high-fidelity simulator, participants provided airway management according to the SARS-CoV-2 protocol. A nonvisible fluorescent marker was used as a surrogate marker of contamination. We assessed ultraviolet light visualization of the fluorescent marker after doffing and satisfaction with donning, use during simulation, and doffing. We found that after doffing, markers were not visualized on any of the participants and that the median satisfaction scores of the alternative and standard BIG (sBIG) were 4 [interquartile range (IQR) = 1–5] and 4 (IQR = 2–4), respectively. The results suggest the suitability and acceptability of the alternative BIG (aBIG) for use by ED personnel. Abstract : Supplemental digital content is available in the text.